2021
DOI: 10.1007/s00402-021-03926-9
|View full text |Cite
|
Sign up to set email alerts
|

Migration characteristics of the Corail hydroxyapatite-coated femoral stem—a retrospective clinical evaluation and migration measurement with EBRA

Abstract: Purpose Uncemented stem migration analysis by EBRA-FCA (Einzel-Bild-Roentgen Analyse, Femoral Component Analysis) has been seen to be a good predictive indicator for early implant failure. In this study, we investigated the migration behavior of a cementless press-fit stem after two years follow-up. Stem type and postoperative gap between collar and femur were evaluated as a risk factor. Methods Applying a retrospective study design, we reviewed all consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Mean subsidence was reported in four studies; meta-analysis on pooled data favored collared stems (MD = −1 mm; 95% CI = −1.6–−0.3) ( 9 , 11 , 51 , 56 ) ( Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mean subsidence was reported in four studies; meta-analysis on pooled data favored collared stems (MD = −1 mm; 95% CI = −1.6–−0.3) ( 9 , 11 , 51 , 56 ) ( Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Full-text screening left eight eligible studies ( 5 , 9 , 10 , 11 , 12 , 13 , 49 , 50 ), and by checking their references, two more relevant studies were identified ( 51 , 52 ). These two studies did not appear in the original search; one was not indexed in any of the databases searched ( 52 ), while the other did not contain the keywords ‘hip replacement’ or ‘hip arthroplasty’ ( 51 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a prospective randomized trial, Reiner et al calculated a mean migration of 1.08 mm (SD 0.93 mm) by RSA for the SL-PLUS MIA stem (Smith & Nephew Orthopaedics AG, Baar, Switzerland) after two years with subsidence mainly occurring during the first six weeks after surgery [32]. While an EBRA-FCA by Stihsen et [16,33]. Ström et al identified a mean subsidence of 1.2 mm for the cementless CLS stem (Centerpulse, Bern, Switzerland) after two years by RSA [34].…”
Section: Discussionmentioning
confidence: 99%